Peran Kehangatan Ibu sebagai Moderator Sosialisasi Emosi dan Regulasi Emosi Anak Usia Prasekolah - Nadia Laras Asih; Lia Mawarsari Boediman (Fakultas Psikologi Universitas Tarumanagara, 2021)
The study aimed to determine the role of emotional socialization in developing preschoolers' emotional regulation moderated by maternal warmth. Participants in this study consisted of 139 mothers who had children aged 3 to 5 years in Indonesia. This study uses a non-probability sampling approach with a moderation analysis technique using Hayes’ PROCESS Macro for SPSS. The instruments used for data collection were The Emotion Regulation Checklist (ERC) to measure mother's perceptions of children's emotions, Coping with Children's Negative Emotions Scale (CCNES) to measure mother's reactions to children's negative emotions, and Parental Acceptance-Rejection Questionnaire-Short Form (PARQ) to measure the level of mother's warmth. The results showed that there is an interaction between emotional socialization and maternal warmth (β= 0.006, t = 2.704, p < 0.05), which plays a role in helping the development of emotional regulation in preschool age. Emotional socialization has a significant effect on the development of emotional regulation in preschool at low maternal warmth levels. That result predicts the low development of emotional regulation of preschool children if the mother has a low level of warmth as well. Although there is a significant interaction between mother's warmth and the socialization of emotions on the development of emotional regulation of preschool children, the role that occurs is not large. This is due to the fact that the two independent variables have several similar characteristics that are likely to influence the interaction value of the two variables.